1161 Streamlining the Patient Journey for Operative Management During COVID 19. (12th October 2021) - Skinner, H; Williams, P; Greenlees, G; Ilyas, C; Schofield, C; Lotia, S; Amtul, N
Abstract: Aim: Leeds, UK is a high-volume acute surgery unit. Emergency operating was drastically affected by the pandemic and time from admission to definitive procedure significantly increased. This intervention aimed to streamline the patient journey from acute admission to the operating theatre. Method: An audit considering delays to transfer, theatre access and recovery discharge, along with the criteria used for 'Hot' theatre was undertaken. Data was collected prospectively between 02/06/2020-06/07/2020 via a standardised proforma. Preliminary results suggested a geographically remote 'hot' theatre was associated with multi-factorial delays so was relocated to more familiar surroundings. This was re-audited between 06/07/2020-06/08/2020 aiming to characterise factors contributing to delay. A dedicated in-hours acute theatres porter was introduced for a trial period. Data was collected retrospectively between 24/08/2020-14/09/2020 and prospectively between 14/09-05/10/2020 via hospital electronic systems. Results: Initially the average time from patient transfer to leaving theatre recovery was 4h6m55s (N = 52). Relocating theatres reduced this to 2h48m04s (N = 74)- an average reduction of 1h18m51s. The greatest reduction was seen in anaesthetic time between 1h17m54s to 41m29s. The introduction of a dedicated porter reduced the average transfer time to theatre from 36 minutes (N = 53) to 21 minutes (N = 68) (p < 0.05). Conclusions: Delay to theatre has a high cost financially and in its effect on patient outcomes. Delays are often multifactorial and robust systems are essential to minimise delays. Patients are best served by well-trained, dedicated 'Acute' team in familiar surroundings. Long-term implementation of dedicated portering service will save time, money and improve patient care.